Neural specialization to English words in Chinese children: Joint contribution of age and English reading abilities - Shuting Huo; Jason Chor Ming Lo; Jie Ma; Urs Maurer; Catherine McBride (Developmental Cognitive Neuroscience, 2023)
N1 tuning to words, a neural marker of visual word recognition, develops by an interaction between age and ability. The development of N1 tuning to a second learnt print is unclear. The present study examined the joint contribution of age and English reading abilities to N1 amplitude and tuning to English print in Chinese children in Hong Kong. EEG signals were recorded from 179 children (six to nine years old) while they were performing a repetition detection task comprised of different print stimuli measuring three types of tuning, i.e., coarse tuning (real word versus false font), fine tuning (real versus nonword), and lexicality effect (real versus pseudo word). Children were assessed in English word reading accuracy (EWR) and English sub-lexical orthographic knowledge (EOK). Results indicated that coarse tuning decreased with age but increased with EWR and EOK. Fine tuning uniquely increased with EOK, and the lexicality effect increased with EWR. At last, higher EWR was linked to less right-lateralized coarse tuning in younger children. Taken together, the findings support the visual perceptual expertise account in the L2 context, in that N1 coarse tuning, fine tuning, and lexicality effect are driven by skill improvement.